Conservative Governments in the Age of Brexit
XVII, 344 p. 2 illus., 1 illus. in color.
Keywords: This book provides the first evaluation of the three Conservative administrations which have been affected, shaped and determined by the age of Brexit. It breaks new ground by collectively analysing the Cameron, May and Johnson governments in an era of political and social shock and disruption, caused by the phenomenon of Brexit. As an edited collection, the book brings experts together who explain the complexities of ideas, leadership, votes, policy areas and territorial politics in an accessible and concise fashion. Contributors consider the continuities and discontinuities in Conservative Party ideas and political action. Matt Beech is Reader in Politics & Director of the Centre for British Politics at University of Hull, UK, and IES Senior Fellow at UC Berkeley, USA. Simon Lee is Senior Lecturer in Politics at University of Hull, UK.